Distracted parenting: How do parents’ emotional regulation and problematic smartphone use contribute to the interruptions of parent-child interactions? - Bodrožić Selak, Matea; Merkaš, Marina; Žulec Ivanković, Ana (Human Technology, 2024)
This study aimed to examine the associations between parents’ difficulties in emotion regulation, risk for smartphone addiction, and interruptions of parent-child interactions. The sample comprised 281 parents (80.9% mothers) who participated in the project “Digital technology in the family: patterns of behavior and effects on child development”. Parents completed the Difficulties in Emotion Regulation Scale (DERS-16; Bjureberg et al., 2016) and the Smartphone Addiction Scale (SAS-SV; Kwon et. al., 2013). Additionally, parents rated how often they use and check their smartphones during parent-child interactions on a newly developed scale as an indicator of interruptions. The results show that parents with greater emotion regulation difficulty have a greater risk for smartphone addiction and report a higher frequency of using and checking their smartphones during parent-child face-to-face interactions. Thus, there is a significant indirect effect of emotion regulation challenges, through risk for smartphone addiction, on interruptions of interactions between parents and children. The findings are further examined within the context of parents’ characteristics that may be risk factors for the prevalence of interruptions of parent-child interactions.